El box y su incidencia en el desarrollo físico de los estudiantes 1º de bachillerato de la Unidad Educativa Francisco Huerta Rendón de la Ciudad de Babahoyo, Provincia de los Ríos periodo 2015 – 2016 - Saac Rosado, Luis Enrique (2016)
The research titled "The box and its impact on the physical development of students 1st high school of the Education Unit" Francisco Huerta Rendon "Babahoyo city, province of the Rivers period 2015 to 2016" is an important topic, review the special considerations that reveal the practice of adopting Box in students under study, as well as the real impact of this sport specialty in physical development of learners. The result reached in the research activity undertaken can be classified as current, as well as being covered with a significant importance, the concrete in the determination of the specific processes in the area of the box for the effectiveness of physical development in students 1 baccalaureate the educational unit "Francisco Huerta Rendón. For the development of the research they were selected and applied theoretical methods and empirical level of scientific research. methods and empirical level of scientific research.